2020
DOI: 10.1039/d0ta07751h
|View full text |Cite
|
Sign up to set email alerts
|

NIR driven fast macro-damage repair and shear-free reprocessing of thermoset elastomers via dynamic covalent urea bonds

Abstract: Fast macro-damage repair and shear-free reprocessing of thermoset elastomers are achieved through NIR induced solid-to-fluid transition based on dynamic covalent urea bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…18 Furthermore, they found that classical covalent urea bonds formed by primary amine and isocyanate can endow these thermoset polyurea materials with macro-damage repair and shear-free reprocessing under NIR driven conditions. 18,19 However, it is highly desirable to prepare cross-linked polymers based on conventional chemical bonds, which can give these polymers exceptional recyclability, along with excellent mechanical properties, such as superior breaking strength and elongation capacity. To date, no reports have yet proposed mechanically robust and recyclable conventional thermosetting polyurea elastomers (TPUEs) that were prepared using commercial raw materials and contained only polyether amine and isocyanate.…”
Section: Introductionmentioning
confidence: 99%
“…18 Furthermore, they found that classical covalent urea bonds formed by primary amine and isocyanate can endow these thermoset polyurea materials with macro-damage repair and shear-free reprocessing under NIR driven conditions. 18,19 However, it is highly desirable to prepare cross-linked polymers based on conventional chemical bonds, which can give these polymers exceptional recyclability, along with excellent mechanical properties, such as superior breaking strength and elongation capacity. To date, no reports have yet proposed mechanically robust and recyclable conventional thermosetting polyurea elastomers (TPUEs) that were prepared using commercial raw materials and contained only polyether amine and isocyanate.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a lot of organic silicone elastomers with a self-healing property have been reported recently. One typical fabrication is carried by chain expansion of the amino terminating polysiloxane with pyridine amide, pyridine dialdehyde, isocyanate, , or the Michael addictive reaction . The elastomers are self-healable with the existence of single/double/multiple dynamic bonds with metal–ligand coordination , and hydrogen bonding through functionalization. , However, some designs usually require specific and expensive small molecule chemical agents or other intricate synthesis steps.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of dynamic covalent bonds into the covalently cross-linked polymer networks is considered an effective approach to provide an exceptional combination in terms of mechanical performance and processability. , Such materials, bridging the gap between thermosets and thermoplastics in the classical category of polymers, are called covalent adaptable networks (CANs) . Particular focus has been on the synthesis of CANs employing various types of dynamic covalent bonds and the control of their network structures for self-healing and/or reprocessing. In addition, with deeper understanding of chemical stress–relaxation and solid-state plasticity of the CANs, versatile applications have been presented, spanning from self-healable and recyclable structural materials to more advanced smart materials including thermadapt shape memory polymers (SMPs), reprogrammable liquid crystalline elastomers (LCEs), and multifunctional hydrogels . In recent years, it has been demonstrated that the mechanical performance of CANs can be further improved by adopting of the biomimetic strategy utilizing sacrificial noncovalent interactions. However, in most of these cases, the noncovalent bonds (e.g., H-bonding and metal–ligand coordination groups) were explicitly established as separate, orthogonal functional groups relative to the dynamic covalent bonds (e.g., ester, boronic ester, disulfide, olefin, and silyl ether groups), thereby requiring careful design of the network structures and compositions.…”
Section: Introductionmentioning
confidence: 99%